Surgical Rehabilitation of a Posttraumatic Iris Cyst, Cataract and Astigmatism Patient - A. L. Onishchenko; V. K. Potehin; N. A. Vershinina (Oftalʹmologiâ)
Injuries cause serious disturbance of the form and function of the organ of vision due to the damage and accompanying or remote complications and therefore have a high proportion to the structure of low vision, blindness and disability. One of the complications of penetrating wounds of the eye is iris cysts. Iris cyst can increase and cause pupillary block, secondary glaucoma, uveitis, corneal dystrophy, and therefore it requires surgical intervention. The goal of surgical treatment of an iris cyst is to ensure complete removal of the cyst.Objective: to estimate the clinical and functional results of treatment in a posttraumatic iris cyst, posterior subcapsular cataract and myopic astigmatism patient.Patient and methods. Patient B., 49 years old with posttraumatic retention iris cyst, posterior subcapsular cataract, compound myopic high astigmatism was examined. To determine the tactics of surgical treatment of the patient, a complex of General ophthalmology was performed (visometry, IOP measurement, autorefractometry, biomicroscopy, ophthalmoscopy), as well as special (B-scanning, optical coherence tomography of the retina) research methods. The follow-up period was 1 year.Results and discussion. To improve visual functions and prevent the development of secondary glaucoma, the patient was offered surgery — excision of the iris cyst and cataract phacoemulsification with toric intraocular lens. Simultaneous carrying out of two stages of the operation reduced the risks of postoperative complications and shorten the rehabilitation period.Conclusion. Positive optical and therapeutic effects were achieved as a result of the surgical treatment 44 years after an open eye injury: the eye is calm, the iris cyst is not detected, visual acuity has increased. The postoperative period showed the saving the stable and high visual and functional result with no recurrence of the iris cyst.